2023
DOI: 10.1007/s11769-023-1333-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal Evolution and Influencing Factors of Digital Financial Inclusion: County-level Evidence from China

Abstract: The vigorous development of information and communications technology has accelerated reshaping of the financial industry. The COVID-19 pandemic has further catalyzed the demand for digital financial services. Digital financial inclusion relies on information technology to overcome spatial limitations. In this case, the research question is whether it adheres to the spatial laws governing conventional financial activities. This study uses exploratory spatial data analysis and a geographical detector to elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Finally, digital financial inclusion can promote the quality of economic growth in neighboring regions. Many studies have confirmed that digital financial inclusion and the quality of economic growth have significant spatial autocorrelation [ 74 , 87 ], and digital financial inclusion has a positive spatial spillover effect on farmers’ income growth [ 88 ]. Aziz and Naima (2021) concluded that although digital services have improved the access to financial services, these services have not been fully utilized due to a lack of basic connectivity, financial literacy, and social awareness [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, digital financial inclusion can promote the quality of economic growth in neighboring regions. Many studies have confirmed that digital financial inclusion and the quality of economic growth have significant spatial autocorrelation [ 74 , 87 ], and digital financial inclusion has a positive spatial spillover effect on farmers’ income growth [ 88 ]. Aziz and Naima (2021) concluded that although digital services have improved the access to financial services, these services have not been fully utilized due to a lack of basic connectivity, financial literacy, and social awareness [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tobler's First Law of Geography states that all things are spatially correlated with other things. Many studies have confirmed that digital financial inclusion has the characteristics of cross-space-time transmission and significant spatial effects [ [73] , [74] , [75] ]. Owing to the continuous expansion of the Internet and big data, digital financial inclusion has spillover effects on other industries, resulting in greater value for participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…where y is the comprehensive CF value; n is the number of evaluation factors; and ∆ i is the importance of evaluation factor i, calculated by the Formula (2). In this study, building upon the foundational deterministic coefficient model, the deterministic coefficient values for each evaluation factor are determined using Equation (1). Utilizing the multi-value extraction to point function in ArcGIS, deterministic coefficient values associated with each evaluation factor are mapped onto each sample dataset.…”
Section: Weighted Linear Combinationmentioning
confidence: 99%
“…Its distinct geographical and geological environment and its topography are the primary causes behind the frequent occurrence of geological disasters in the region. Areas with mountainous plateau terrain are prone to geological hazards such as collapses, landslides, and debris flows, posing significant threats to national economic development, the safety of lives and properties, as well as causing substantial damage to infrastructure and the ecological environment within the affected areas [1]. Among geological disasters in China, slope-related incidents rank as the second most prevalent after earthquakes [2].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the county becomes a regional unit with earlier, faster, more widespread and larger-scale population contraction in China. Meanwhile, the social, economic and ecological environmental effects generated by population contraction are more comprehensive, more typical, more prominent and stronger [2][3][4]. By comparing the data of the sixth and seventh national census, it is found that from 2010 to 2020, the proportion of the country s permanent resident population shrinking in counties was 53%, the working-age population in more than 70% of counties decreased to varying degrees, and the growth rate of the working-age population in more than 96% of counties was lower than that of the permanent resident population [4].…”
Section: Introductionmentioning
confidence: 99%